Strategies for integrating a web-based learning environment based on authentic learning in distance learning for elementary school students - Hidayati, Abna; Eldarni; Solfema; Handrianto, Ciptro; Sunarti, Vevi (Journal of Education and e-Learning Research, 2023)
This research aimed to find a strategy to integrate web-based learning based on authentic learning by identifying the dominant factors regarding teachers’ authentic activities. The research method was a teacher survey that used web-based learning. Questionnaires were given to 100 teachers regarding the use of authentic activities. The questionnaire was tested for validity and had a high load factor of more than 0.6. Authentic learning had an effect of 0.689. The data was processed by factorial analysis to obtain the dominant value. Furthermore, a strategy to integrate web-based learning was developed in learning. The results showed that the dominant authentic learning activities used were real-world activities, integrated assessment, various sources and final product design. It can be concluded that using web-based learning applications based on authentic learning provides real-life experiences for students and supports learning to be more meaningful.